2016
DOI: 10.1210/en.2015-1793
|View full text |Cite
|
Sign up to set email alerts
|

Activin Enhances α- to β-Cell Transdifferentiation as a Source For β-Cells In Male FSTL3 Knockout Mice

Abstract: Diabetes results from inadequate β-cell number and/or function to control serum glucose concentrations so that replacement of lost β-cells could become a viable therapy for diabetes. In addition to embryonic stem cell sources for new β-cells, evidence for transdifferentiation/reprogramming of non-β-cells to functional β-cells is accumulating. In addition, de-differentiation of β-cells observed in diabetes and their subsequent conversion to α-cells raises the possibility that adult islet cell fate is malleable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The literature reporting quantitative data on human bihormonal cells is limited 21,22 , and previous studies have not considered the possibility that bacterial pathogens may contribute to their emergence. Two possible means to induce conversion of α-cell to β-cell or β-cell to α-cell have been identified: (1) near complete ablation of β-cells using chemical agents 13,45,46 and (2) forced expression/deletion of βor α-cell specific transcription factors and/ or deletion of Dnmt1 or FOXO1 transcription factor in β-cells in mice [14][15][16]18,19 . We found that Pg/gingipain is not detected in mouse α-cells and at a low % in human α-cells, making it unlikely that Pg directly induces αto β-cell transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reporting quantitative data on human bihormonal cells is limited 21,22 , and previous studies have not considered the possibility that bacterial pathogens may contribute to their emergence. Two possible means to induce conversion of α-cell to β-cell or β-cell to α-cell have been identified: (1) near complete ablation of β-cells using chemical agents 13,45,46 and (2) forced expression/deletion of βor α-cell specific transcription factors and/ or deletion of Dnmt1 or FOXO1 transcription factor in β-cells in mice [14][15][16]18,19 . We found that Pg/gingipain is not detected in mouse α-cells and at a low % in human α-cells, making it unlikely that Pg directly induces αto β-cell transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of bihormonal cells in animal models has been reported following near complete destruction of β-cells (99% ablation) by chemical agent 13 or by forced expression/deletion of βor α-cell specific transcription factors [14][15][16][17] using conditional knockout and/or lineage tracing mice. Re-differentiation of α-cells from de-differentiated β-cells 18 also represents another means of developing intermediate/bihormonal cells.…”
mentioning
confidence: 99%
“…Bramswig et al treated α cells with Adox, a histone methyltransferase inhibitor, and achieved partial conversion to insulin + cells (Bramswig et al, 2013). Recently it was observed that Activin enhanced α to β cell reprogramming (Brown et al, 2016), indicating that signaling regulation may contribute to α to β cell reprogramming.…”
Section: α To β Cell Reprogrammingmentioning
confidence: 99%
“…It is well known that islet cells convert to the cells with other characteristics under various artificial conditions. Epigenomic manipulation is thought to provide a path to alpha- to beta-cell reprogramming 4 , and searches for materials that promote alpha- to beta-cell conversion are also progressing 5 7 . Genetic manipulations of transcription factors are also often conducted to induce transdifferentiation of islet cells.…”
Section: Introductionmentioning
confidence: 99%